A Survey of Bee Species Found Pollinating Watermelons in the Lower Rio Grande Valley of Texas. (17th April 2012) - Henne, C. S.; Rodriguez, E.; Adamczyk, J. J.
Abstract : Using a combination of flower traps and visual observations, we surveyed three watermelon ( Citrullus lanatus (Thunb.) Matsum. & Nakai) fields in the Lower Rio Grande Valley to determine what bees inhabit this crop in this region. No managed honey bee ( Apis mellifera L.) hives were in any of the fields; however, two contained managed hives of the common eastern bumble bee, Bombus impatiens (Cresson). A total of 15 species were collected or observed from all three fields combined. Of these species, only four were found to be very abundant: Agapostemon angelicus Cockerell /texanus Cresson, A. mellifera, Lasioglossum coactum (Cresson), and Melissodes thelypodii Cockerell. Apis mellifera comprised 46% of all bees collected from all three fields combined and was highly abundant in two of the three fields. In the third field, however, A. mellifera and Agapostemon angelicus/texanus were equally abundant. Surprisingly, B. impatiens comprised only 1% of the total bees surveyed in all three fields combined, despite two of the fields having several managed hives each. As B. impatiens is not native to this region, it was not surprising that none were collected or observed in the field with no managed hives.